EFFECT OF GOLIMUMAB ON IMMUNOLOGICAL MARKERS FOR BONE METABOLISM AND ON ARTERIAL STIFFNESS IN PATIENTS WITH RHEUMATOID ARTHRITIS - L. A. Knyazeva; N. Damjanov; L. I. Knyazeva; N. S. Meshcherina; I. I. Goryainov (Научно-практическая ревматология, 2018)
Objective: to evaluate the effect of golimumab (GLM) on the receptor activator of NF-κB ligand (RANKL)/osteoprotegerin (OPG) transmembrane molecular system and arterial stiffness in patients with rheumatoid arthritis (RA).Subjects and methods. Thirty-six patients with RA were examined and randomized into 2 groups based on disease duration (less than or more than 2 years). The serum levels of OPG, and RANKL, were investigated. Dual-energy X-ray absorptiometry and pulse wave contour analysis were performed before and 52 weeks after GLM treatment.Results and discussion. Group 1 patients demonstrated increased serum OPG levels that were on average 3.6 times higher than in the controls (р=0.005) and 2.1 times higher than in Group 2 (р=0.01). In Group 2 patients, the RANKL concentration was 9-fold higher than that in the controls (p=0.001) and 30.6% higher than in Group 1 (p=0.01). The examinees were found to be diagnosed with subclinical damage to the great arteries (increases in augmentation index (AIp), stiffness index (SI), and reflection (RI) index), which progressed with a longer RA duration. After GLM treatment, serum OPG and RANKL levels decreased in Group 1 patients by 2.1- (p<0.001) and 1.7-fold (p<0.01), respectively. In Group 2, the level of RANKL dropped by 32.2% (p<0.01), without significant OPG concentration changes. After GLM treatment, the pulse wave contour analysis parameters in Group 1 did not differ from those in the controls; Group 2 showed significant decreases in AIp by an average of 1.8 times (p<0.01), in SI by 1.2 times (p<0.01), and in RI by 1.6 times (p<0.01).Conclusion. GLM treatment in RA patients is accompanied by a lower imbalance in the RANKL/OPG transmembrane molecular system and exerts a vasoprotective effect on the large elastic vessels (reductions in AIp and SI) and small muscular arteries (a decrease in RI).